Margin dan Efisiensi Pemasaran Cabe Jamu di Kabupaten Sumenep - Hasan, Fuad; Ihsannudin, Ihsannudin; Destiarni, Restri Prastika (Universitas Galuh, 2024)
Long pepper have a very large export market potential and high prices, but some farmers in Sumenep intend not to continue their long paepper farming because the income they earn was not much. The size of farmers' income can be influenced by product marketing channels. This research aims to determine the marketing channels, margins and marketing efficiency of long pepper in Madura, starting from farmers to exporters. The research was conducted in Sumenep Regency as the largest long pepper producer in Madura. Research respondents were farmers taken using a purposive sampling technique and marketing institutions (intermediary traders and exporters) taken using a snowball sampling technique. The instrument used to collect primary data is a questionnaire. Marketing channels are analyzed descriptively while marketing margins and efficiency are calculated using formulas adopted from references. Marketing efficiency is measured by indicators of farmer's share, cost and profit ratio, and the Acharya model marketing efficiency index. The research results show that there are three levels of marketing channels, namely 0-level, 1-level model A (the intermediary is the wholesaler and the final destination is the herbal medicine producer), B (the intermediary is the wholesaler and the final destination is the exporter), C (the intermediary is the processor and the final destination is the exporter), and 2-level where the intermediary traders are small and large collectors. The largest marketing margin is in the 1-level model C channel (IDR 33,000), while other channels are IDR 4000. All efficiency indicators show that all marketing channels are efficient.